Auger electron spectroscopy analysis of grain boundary microchemistry in an Al–Cu–Li alloy. (1st July 2016) - Ott, Noémie; Yan, Yuanming; Ramamurthy, Sridhar; Kairy, Shravan; Birbilis, Nick
Abstract: In situ impact fracture combined with Auger electron spectroscopy (AES) was employed to determine grain boundary (GB) microchemistry, namely lithium (Li) concentration, for an Al–Cu–Li alloy. The Li/Al ratio of GBs in the naturally aged condition was revealed to be significantly higher than in the overaged condition (or in the bulk alloy). GB fracture surfaces for the naturally aged alloy were depleted in Cu, whereas in the overaged condition the GB fracture surfaces were depleted in Li and enriched in Cu relative to the bulk composition. These findings are discussed in the context of intergranular corrosion and the precipitation sequence in Al–Cu–Li alloys. Graphical abstract: